Handbook of forensic neuropsychology - Horton, Arthur MacNeill, 1947-; Hartlage, Lawrence C. (Springer Pub. Co., 2003)
This volume explains neuropsychological services to the population of brain injured adults and children who enter the legal system. It provides a comprehensive, well-integrated treatment of this new area of interest in neuropathology-psychopathology relationships, and examines the research knowledge base, which supportsthis investigation. After exploring the foundations of forensic neuropsychology, The authors discuss the reliability of test data as well as norms, decision-making, and malingering. The Handbook also considers ethical issues, discovery depositions, courtroom testimony, and profe.